EFFECT OF ACID CONCENTRATION AND ROTATION RATE ON PB LEACHING FROM GALENA ORES - Sundari, Rita; Dahani, Wiwik; Marwanza , Irfan; Subandrio, Subandrio; Herdiyanto, Rizky B. (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2025)
This research is related to lead (Pb) leaching from galena ores using acid leaching method. The galena ores have been treated through pyrometallurgy method by roasting at 600oC 1h to yield galena concentrate. The Pb concentration has been determined by AAS (Atomic Absorption Spectrophotometry) using acid leaching method. This study has observed the effect of leaching acid concentration (acetic and sulfuric acids) and rotation rate on Pb leaching at 50oC 45 min. This study shows that varied acetic acid concentrations gave more effect on Pb extraction. Optimum condition achieved for 2.0 M acetic acid for all given rotation speeds (200 rpm, 300 rpm, and 400 rpm). For sulfuric acid leaching, optimum condition achieved at 1.0 M H2SO4 at 400 rpm. From the results, it is apparent that varied rotation speed (200 rpm, 300 rpm, 400 rpm) gave lesser effect on Pb leaching rather than varied acid concentration effect (0.5 M, 0.75 M, 1.0 M, 2.0 M, and 3.0 M). In addition, the XRF (X-Ray Fluorescence) analysis on galena ores shows the existence of lanthanum, ytterbium, and europium (rare earth elements) in significant amount since rare earth elements displays important role in modern industry for nuclear battery, dental apparatus, microchips, hybrid vehicles, catalyst for cracking, audio device, and ceramic agent. Statistical and numerical analysis are briefly included in this study to determine the dominant factor and process optimization.